Validity and Reliability of Functional Independence Measure for Children (WeeFIM) for Children With Cerebral Palsy. (15th January 2022) - Jang, Jong-Sik; Jeon, Ju-Yeong; Kim, Hyub; Kim, Geon-Woo
Purpose: This study was conducted to verify the validity and reliability of the Functional Independence Measure for Children (WeeFIM) for children with cerebral palsy by verifying the construct validity, difficulty, suitability, and cultural differences using Rasch analysis.Methods: From May 1, 2015, to February 27, 2020, 105 children with cerebral palsy aged 6 months–95 months (7 years and 11 months old) from Hospital Y located in Korea were included. In WeeFIM, 18 items were divided into 3 areas: Self-care 8 items, Motor 5 items, and Cognition 5 items. Analysis and separation reliability were analyzed.Results: In theSelf -care area, theGrooming item and in the Motor area, the Transfer (Tub, Shower) item were judged as inappropriate items, and the order of difficulty was arranged without excluding the unsuitable items. In Self-acre, the most difficult item was Bathing, the easiest items were Eating andBladder management, and the separation reliability was .87, the most difficult item in Motor was Stair, and the easiest item was Locomotion, and the separation reliability was .99. In Cognition, the most difficult item was Problem Solving, the easiest item was Communication, and the separation reliability was .95.Conclusion: The reliability and validity of WeeFIM was verified for children with cerebral palsy by applying Rasch Analysis. In future research, it is thought that additional research should be conducted by dividing the children by age and type so that they can be generalized.